Reported risky sexual practices amongst female undergraduate students in KwaZulu-Natal, South Africa - Hoque, Muhammad Ehsanul (Afr J Prim Health Care Fam Med, 2011)
BACKGROUND: In South Africa, youths aged 15–24 years are at a higher risk of HIV infections than other age groups, and female youths are at a greater risk than their male counterparts. An essential step in controlling the pandemic of HIV and other sexually transmitted infections (STIs) is to help adolescents to reduce or avoid unsafe sexual practices. OBJECTIVE: This study was designed to establish risky sexual practices amongst female undergraduate students. METHOD: This was a descriptive cross-sectional study carried out in September 2009 amongst full-time female undergraduate students. A multi-stage sampling method was used to recruit 391 students for the study. RESULTS: The mean age of the students was 21.4 ± 3.2 years (range 17–45 years). More than half (52.4%) of the students were sexually active. The median age at first sexual intercourse was 19.0 years (range 12–24 years). Participants who had multiple sexual partners had a median of 2 (range, 2–4) sexual partners. The majority (89.3%) of the students used contraceptives. Almost half (41.5%), sometimes or rarely, used contraceptives during sex. With regard to substance use, 57.5% and 6.9% respectively drank alcohol and used drugs. Sexually active students had 1.5 times (OR = 1.5, p = 0.04), (OR = Odds Ratio), more chances of consuming alcohol than those who were not sexually active. Students with multiple sexual partners were 7 times more likely to consume alcohol compared to those who did not have multiple partners (OR = 6.9, p = 0.004). Students with multiple sexual partners had 3.5 times more chances of taking drugs compared to students with one steady partner (OR = 3.5, p = 0.038). CONCLUSION: A large number of female university students are engaging in risky sexual practices. University Management should concentrate on developing and implementing policies to promote safer sexual practices, in particular targeting consequences of STIs and HIV and methods to minimise the risk.